A fluorogenic probe for dynamic tracking of lipid droplets' polarity during the evolution of cancer. (18th February 2021) - Liu, Cong; Yin, Junling; Lu, Bingli; Lin, Weiying
Abstract : Exploring the changes in the polarity of intracellular lipid droplets (LDs) during the evolution of cancer is important for cancer detection and treatment. Abstract : Exploring the changes in the polarity of intracellular lipid droplets (LDs) during the evolution of cancer is important for cancer detection and treatment. Therefore, we designed and synthesized a new type of polarity-sensitive fluorescent probe, CTPE, which uses coumarin as the polarity-sensitive group and tetraphenylethylene as the electron-donating group to target LDs. Due to its special intramolecular charge transfer mechanism, CTPE emitted a weak green fluorescence in high-polar solvents, and a strong green fluorescence in low-polar solvents, thus exhibiting a drastic change in fluorescence signal as a function of the solvent polarity. In virtue of the probe CTPE, tumorous tissues have been successfully identified from normal ones and the decrease in LDs' polarity could be revealed with the evolution of cancer. Moreover, the changes in the LDs' polarity in drugs-treated tumor were observed at the tissue level, endowing its capacity for anti-cancer drug efficacy evaluation. This work provides a promising imaging tool for LDs tracking in cancer research and clinical diagnosis.